2006
DOI: 10.2460/javma.228.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical characteristics and bacterial isolates in dogs with bacterial keratitis: 97 cases (1993–2003)

Abstract: Data suggested that administration of ciprofloxacin or a combination of a first-generation cephalosporin and tobramycin may be used in the treatment of bacterial keratitis while awaiting results of bacterial culture and susceptibility testing. Evidence suggests that current methods of medical management of bacterial keratitis are not associated with increased antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
117
7
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(162 citation statements)
references
References 17 publications
14
117
7
12
Order By: Relevance
“…All of the 12 Pseudomonas isolates were resistant to fusidic acid, and 7 were resistant to gentamicin. This differs from Tolar et al (2006) who found that 25 out of 25 P.aeruginosa isolates from canine corneal ulcers were sensitive to gentamicin however there are concerns that there is an increase in the resistance to the aminoglycosides by P.aeruginosa isolated from infected human eyes (Gelender et al 1984). This has important implications in the treatment of progressive corneal ulcers where gentamicin is indicated, and highlights the importance of therapeutic selection based on culture and sensitivity results.…”
Section: Antibiotic Susceptibility Testcontrasting
confidence: 46%
“…All of the 12 Pseudomonas isolates were resistant to fusidic acid, and 7 were resistant to gentamicin. This differs from Tolar et al (2006) who found that 25 out of 25 P.aeruginosa isolates from canine corneal ulcers were sensitive to gentamicin however there are concerns that there is an increase in the resistance to the aminoglycosides by P.aeruginosa isolated from infected human eyes (Gelender et al 1984). This has important implications in the treatment of progressive corneal ulcers where gentamicin is indicated, and highlights the importance of therapeutic selection based on culture and sensitivity results.…”
Section: Antibiotic Susceptibility Testcontrasting
confidence: 46%
“…The main genus of microorganisms isolated in ophthalmic changes animals are Staphylococcus (Prado et al, 2005); Wang et al, 2008), followed by Streptococcus, Pseudomonas and Escherichia coli (Tolar et al, 2006) In dogs, Staphylococcus pseudintermedius is identified as the main agente (Montiani-Ferreira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The previous use of eye drops with antibiotics and steroids, administered as inadequate frequency or period, are associated with external eye diseases and can cause clinical recurrence, with selection and multiplication of eye microbiota, slow healing corneal epithelium, suppression of inflammatory mechanisms and enhancement of corneal ulceration (OLLIVIER, 2003;PRADO et al, 2006;TOLAR et al, 2006;LAUS, 2009;MORALES et al, 2009). …”
Section: Saureus (Staphylococcus Aureus); Sintermedius (Staphylococmentioning
confidence: 99%